Gambaran Faktor Risiko Kejadian Stunting pada Ibu dengan Anak Balita Stunting di Wilayah Kerja Puskesmas Baregbeg - Lala, Lala; Purnamasari, Kurniati Devi; Sastraprawira, Tika (Universitas Galuh, 2024)
Stunting is one of the main nutritional issues that Indonesian toddlers face. The prevalence of stunting in toddlers (children under five years old) was 30.8% in 2018, according to the Basic Health Research (Riskesdas) results. This dropped to 27.67% in 2019 (Indonesian Nutrition Status Survey (SSGI), 2019), and then increased to 24.4% in 2021 (SSGI, 2021). The purpose of this study is to identify the risk factors for stunting in women in the Ciamis Regency working area of the Baregbeg Community Health Center who have stunted children under five in 2024. Descriptive research using a cross-sectional design was the methodology employed. Using a questionnaire, the study's population composed of all the mothers of 36 kids with stunting in the Baregbeg Health Center's working area. The majority of stunted toddlers had a history of exclusive breastfeeding (80.56%), middle class mothers in a middle educational level (55.56%), low parental income (86.11%), low birth weight babies (86.11%), infectious diarrheal diseases (86.11%), poor diet (77.78%), and an unvarried diet (88.88%), based to the research's results. To help to prevent potential problems with the child's growth and development, it is advised that moms of stunted children give their children greater care.